Gator: A Python‐driven program for spectroscopy simulations using correlated wave functions. (17th March 2021) - Rehn, Dirk R.; Rinkevicius, Zilvinas; Herbst, Michael F.; Li, Xin; Scheurer, Maximilian; Brand, Manuel; Dempwolff, Adrian L.; Brumboiu, Iulia E.; Fransson, Thomas; Dreuw, Andreas; Norman, Patrick
Abstract: The Gator program has been developed for computational spectroscopy and calculations of molecular properties using real and complex propagators at the correlated level of wave function theory. Currently, the focus lies on methods based on the algebraic diagrammatic construction (ADC) scheme up to the third order of perturbation theory. An auxiliary Fock matrix‐driven implementation of the second‐order ADC method for excitation energies has been realized with an underlying hybrid MPI/OpenMP parallelization scheme suitable for execution in high‐performance computing cluster environments. With a modular and object‐oriented program structure written in a Python/C++ layered fashion, Gator additionally enables time‐efficient prototyping of novel scientific approaches, as well as interactive notebook‐driven training of students in quantum chemistry. This article is categorized under: Computer and Information Science > Computer Algorithms and Programming Electronic Structure Theory > Ab Initio Electronic Structure Methods Software > Quantum Chemistry Abstract : The Gator program is an easy‐to‐use yet powerful tool to calculate molecular properties and spectroscopies with real and complex response functions using the second‐ and third‐order algebraic diagrammatic construction schemes.